Do parties make a difference? The relationship between government intention and government output in the public policy sphere: the case of governments in Ireland 1977-1997 - Mansergh, Lucy Eleanor (Trinity College (Dublin, Ireland). Department of Political Science, 2004)
Students of representative democracy are not in agreement as to the degree of influence that parties exert over public policy. One possible route by which partisan influence may be investigated is through a case study of pledge fulfilment. I submit that there are seven requirements for a partisan difference to be suggested through this pledge approach. These are as follows; -- 1. parties stand for different policies (Sullivan and O'Connor 1972), -- 2. voters perceive the parties' different stances (Sullivan and O'Connor 1972), -- 3. voters cast their ballots on the basis of the different policy positions on offer (Sullivan and O'Connor 1972), taking into account the reputations of the parties with regard to policy consistency (Downs 1957, Denver and Hands 1992), -- 4. parties in government redeem more of their own policy promises than those of the opposition (Klingemann, Hofferbert and Budge 1994, Thomson 1999), -- 5. parties, if they get into government after the election, generally redeem the policy promises they offered before the election (Sullivan and O’Connor 1972), -- 6. where parties do not remain faithful to their pre-election promises, the voters punish them at the following election (Downs 1957), -- 7. actions promoted in manifestos account for the vast majority of later government actions. In this thesis, I test for all seven requirements over the Irish government terms 1977-2002. I use different methods to test the seven requirements. For the first three and sixth requirements, I rely largely on collated evidence from secondary sources.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin